Influences of mathematical and psychological constructs on mathematics achievement among 8th grade Iranian students - Kamalimoghaddam, Hajar (2016)
The current study explored the critical connections between students’ mathematical problem solving skills, mathematics beliefs, prior mathematics achievements, mathematics self-efficacy and mathematics achievement among 400 middle school students across Iran who were in grade eight. Ten structural equation models, one measurement model and twelve individual models were tested to understand (1) direct and indirect relationships between students’ mathematical problem solving skills, students’ mathematics beliefs, students’ prior mathematics achievement, and students’ mathematics achievements; (2) direct influences of students’ mathematical problem solving skills, students’ mathematics beliefs, students’ prior mathematics achievement on students’ mathematics self-efficacy; and (3) direct relationship between student’s mathematics self-efficacy and students’ mathematics achievements. The structural equation models tested in this study suggested that students’ mathematical problem solving skills, students’ mathematics beliefs, and students’ prior mathematics achievement directly influence students’ mathematics achievements (Chi-sq=2.80, GFI=.94, CFI=.97, AGFI=.91, IFI=.97, NFI=.95, TLI=.96, RMSEA=.06). Also, direct model indicated correlation coefficient from low to high (.11 to .79), factor loading (.56 to .93) and critical ratio more than 1.96 for all of paths. Moreover, students’ mathematical problem solving skills, students’ mathematics beliefs, and students’ prior mathematics achievements indirectly influence students’ mathematics achievement through students’ mathematics self-efficacy (Full Structural Model, Chi-sq=2.49, GFI=.94, CFI=.98, AGFI=.91, IFI=.98, NFI=.96, TLI=.97, RMSEA=.06). Also, mediation model indicated correlation coefficient from low to high (-.08 to .58), factor loading (.57 to .95) and critical ratio more than 1.96 for all of paths). The implications for future research along with the limitations are discussed.